Determination of sex of adult human clavicle by discriminant function analysis in Marathwada region of Maharashtra - Doshi, M. A.; Reddy, Bhaskar B. (International Journal of Research in Medical Sciences, 2017)
Background: Determination of biological sex is one of the most important determinations to be made from human remains and is an essential first step in the development of the biological profile in forensics, anthropology and bioarchaeology. The aim of this study was to determine whether sexing of unknown adult human clavicles can be done by applying values of morphometric parameters and formulae generated by present study on adult human clavicles of known sex and to find out the best parameters for sex determination. Methods: Various metric measurements were recorded using osteo metric board, measuring tape, non-elastic thread, sliding calipers and vernier calipers on adult human clavicles. Results: Sex was correctly estimated by using stepwise discriminant function analysis, for the clavicle 93.3 % of males and 94.4% of females, with a total accuracy of 93.7 %. Direct discriminant function analysis, correct estimated sex for the clavicle was 93.9 % in males and 93.3% in females with a total accuracy of 93.7 %. Conclusions: Present study exhibited better classification accuracy for multiple variables than those of single variables. In the clavicle, the most discriminating variables in stepwise analysis are the mid clavicular circumference, posterior curved length, medial 2/3 and lateral 1/3 junction circumference and Weight. In direct analysis, the single most useful variable was the mid clavicular circumference.